2004
DOI: 10.1016/s0014-5793(04)00378-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant ATPases of the yeast 26S proteasome activate protein degradation by the 20S proteasome

Abstract: The 26S proteasome contains a proteolytic core, 20S proteasome, and its regulatory particle, 19S complex. That regulatory particle contains six ATPases that are involved in unfolding and translocation of substrates to the 20S proteasome's catalytic chamber. We expressed ATPase-encoding genes of the regulatory particle of Saccharomyces cerevisiae and found that some recombinant ATPases can self-assemble into a high-molecular-weight protein complex in Escherichia coli. Purification of the Rpt1Rpt2 hetero-complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To explore more about the general applicability of FATT‐fusion as a way to facilitate soluble expression, six base subunits from the 19S proteasomal complex were individually expressed as either FATT‐ or GST‐fusion proteins. Bacterial expression of these proteins (Rpt1–6) has been very difficult because the individual subunits have a strong tendency to aggregate, and even the solubility‐enhancing GST‐tag showed very limited effects [Fig. (B), panels "GST"].…”
Section: Resultsmentioning
confidence: 99%
“…To explore more about the general applicability of FATT‐fusion as a way to facilitate soluble expression, six base subunits from the 19S proteasomal complex were individually expressed as either FATT‐ or GST‐fusion proteins. Bacterial expression of these proteins (Rpt1–6) has been very difficult because the individual subunits have a strong tendency to aggregate, and even the solubility‐enhancing GST‐tag showed very limited effects [Fig. (B), panels "GST"].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it could be suggested that 20S proteasome first binds with base, which is followed by attachment of lid complex. The ATPases are also required for the assembly of 19S proteasome, since yeast ATPases genes co‐expression in E. coli is able to provide a heterohexameric complex present in the base of 19S . On the basis of mass spectrometry analysis of yeast lid complex, two clusters of 19S assembly intermediates have been identified: first one is composed of Rpn5, 6, 8, 9, 11 and the other one is of Rpn3, 7, 12, and 15, in which interaction between Rpn3 and 5 joins both the clusters .…”
Section: Understanding and Synchronization Of The Organization Of A Cmentioning
confidence: 99%
“…The main eukaryotic degradation machinery, the 26S proteasome, specifically degrades ubiquitinylated proteins (Miller and Gordon, 2005). Proteolysis is performed by the ATPindependent peptidase activity of the 20S core of the proteasome, whereas substrate specificity is mediated by the 19S regulatory particle consisting of a base complex which confers ATPase and chaperon activity and a 26S lid complex of so far unknown function (Takeuchi and Tamura, 2004). Proteins are targeted for degradation by poly-conjugation of the small ubiquitin protein.…”
Section: Introductionmentioning
confidence: 99%